التفاعل الوظيفي بين النظام الحزبي و النظام السياسي - بالنور, علاء الدين (University of Eloued جامعة الوادي, 2021)
تَعتبِر هذه الدراسة المنظور الوظيفي إطاراً تحليلياً ملائماً لمعالجة ظاهرة التفاعل بين النظام الحزبي والنظام السياسي. إذ من خلاله تعالج هذه الدراسة مسألة التفاعل معالجة علمية ومنهجية، وذلك من خلال العلاقة السببية القائمة على أساس التأثير المتبادل بين هذين المتغيرين. كما تشير هذه الدراسة إلى أن هذا التأثير تتحكم فيه في الواقع جملة من المحددات : كخصوصية الحقبة التاريخية التي يتفاعل فيها النظامان، و كذا محدد مواصفات القدرة على التأثير، التي تجعل أحد المتغيرين يتفوق على المتغير الأخر في التأثير عليه. بالإضافة إلى محددات أخرى لها صلة إماّ بالنظام الحزبي أو بالنظام السياسي. حيث تناقش هذه الدراسة من جهة : عدد الأحزاب و بنيتها الداخلية و ميكانيكية النظام الحزبي كمحددات لتأثير النظام الحزبي في النظام السياسي، كما تناقش من جهة أخرى : شكل الحكم و النمط الفيدرالي و نمط النظام الانتخابي كمحددات لتأثير النظام السياسي في النظام الحزبي. علاوة على ذلك، تتناول هذه الدراسة محددًا أخر لهذا التفاعل يتمثل في المساهمة الوظيفية للأحزاب في استيفاء المتطلبات الوظيفية للنظام السياسي، لا سيما في استيفاء وظيفة الشرعية والاستقرار و وظيفة الاستخلاف السياسي و الوظيفة المنبرية. الكلمات المفتاحية:- التفاعل الوظيفي، التداخل البنيوي، النظام الحزبي، النظام السياسي، المتطلبات الوظيفية. This Study considers the functional perspective as an appropriate analytical framework for treating the phenomenon of the interaction between the party system and the political system. Through this perspective, this study handles the interaction issue scientifically and methodologically through the causal relationship based on the mutual influence between these two variables. Moreover, this study indicate that this effect is controlled by a number of determinants, such as the specificity of the historical era in which the two systems interact, as well as the characteristics of impact capacity which makes one variable outperforms the other variable in affecting it. In addition to other determinants related to either the party system or the political system. On one hand, this study discusses the number of parties, their internal structure and the mechanics of the party system as determinants of the influence of the party system on the political system. On the other hand, this study discusses the form of government, the federal pattern and the electoral system type as determinants of the political system influence on the party system. Furthermore, this study deals with another determinant of this interaction concerned with the functional contributions of the parties in fulfilling the functional requirements of the political system, especially in fulfilling the function of legitimacy-stability, the political succession function and tribunitian function. Keywords: Functional interaction, structural overlap, party system, Political system, functional requirements.
مجلد12، عدد1
Keywords: التفاعل الوظيفي ; التداخل البنيوي ; النظام الحزبي ; النظام السياسي ; المتطلبات الوظيفية; Functional interaction; structural overlap; party system; political system; functional requirements.